JERITAN PEREMPUAN YANG TERKUNGKUNG SISTEM PATRIARKI DALAM KUMPULAN CERITA PENDEK AKAR PULE: SUATU TINJAUAN FEMINISME RADIKAL - Zahratul Umniyyah (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
This study discusses two short stories part of Akar Pule anthology written by Oka Rusmini. In this study, the writer attempts to reveal, analyze, dan describe physical and psychological oppressions experienced by the female character. In this study the writer uses qualitative method as research method. The author voices her thoughts by presenting the female characters and their problem caused by male characters (men). In these short stories female characters (women) are placed in weaker position than men. The patriarchal system which is deeply rooted in Balinese culture gives more oppression towards women making Balinese women more powerless and forcing them to obey the customs that disadvantage them.